TOURISM PRODUCT DEVELOPMENT IN ECOLOGICALY AND CULTURALLY FRAGILE AREAS – OBSERVATIONS FROM KERALA IN INDIA - M.P.Saji and N.Narayanasamy (University of Kelaniya, 2010)
For economically poor but resource rich countries, tourism has become a vital sector to be considered for regional development. In the post-modern world, there seems to be an ever increasing urge for experiencing authentic life styles and environment – a search which is obvious to end up in locations and communities that were ecologically and culturally enclosed so far, so that it had not altered yet. This taste of more diversified and specialized experience makes many of the culturally and ecologically rich regions attractive in contemporary tourism market. The new tourism styles like Eco-tourism, Cultural tourism, Rural tourism, (indeed too many) have become synonym with the growth of tourism in several countries. However the real challenge before policy makers and the industry is to manage and strike a balance between conservation, recreation and regional development. In this context, the paper tries to explore through various alternative tourism concepts like eco-tourism and cultural tourism and observe its actual practices in Kerala, the southern most states of India, which has initiated several innovative tourism models. After analyzing the pros and cons tourism initiatives in the state, the paper seeks to appreciate and present the approaches that could be used as a base for tourism product development and management in ecologically and culturally fragile area.